R&D investment: A dynamic efficiency approach in the EU countries - Saavedra, David Paz; Fuente, Marta De La; Fernandez, Xose Luis; Millan, Pablo Coto (The Economics and Finance Letters, 2024)
This paper aims to analyze the role of research and development (R&D) in the production efficiency of European Union Member States. Utilizing Bayesian methods within a dynamic framework, the study jointly estimates production functions and efficiency for a sample of 27 countries over the 2000–2021 period. The findings reveal that human capital investment exhibits a higher output elasticity compared to physical capital investment. Additionally, the results indicate that inefficiencies persist due to escalating costs—both monetary and temporal—as inputs expand. Across the studied countries, an upward trend in R&D expenditure is associated with increasing technical efficiency levels, establishing a positive relationship between R&D spending and technical efficiency scores. Geographically, eastern and southern European regions exhibit lower average efficiency levels. These insights are crucial for policymakers seeking to foster innovation-driven policies, highlighting the importance of maintaining or increasing R&D spending to achieve the economic and social objectives of the European Union. Through appropriate R&D policies, policymakers can enhance technical efficiency, ensure the EU's global competitiveness, and promote more equitable development across the Union.